Memahami Formulasi Aqidah Qurani Dalam Tradisi Intelektual - Miskahuddin, Miskahuddin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
Religion respects every servant of God using common sense to think about something according to the framework of Aqeedah which is based on the values of the Qur'an. The personality of a Muslim is considered noble and quality if it is able to formulate the Aqeedah in its Intellectual Property in a comprehensive and universal manner. There are no religious teachings restricting people to always think of seeking the truth that God loves. Thinking about using sharp and quality intellectuals to improve or perfect their worship activities so that Allah receives all their acts of worship is an obligation in religion. The awareness of thinking to get the values of intellectual truth in his life is a necessity that cannot be separated from the substance of religion and the urge of Islamic faith. Understanding the Aqeedah correctly and formulating it in the intellectual tradition as a whole, will be able to provide positive solutions in efforts to solve various forms of social problems in human life and the environment.